EMOTIONAL SCHEMA THERAPY - ROBERT L. LEAHY (Moscow State University of Psychology and Education, 2021)
Cognitive therapy has often been criticized as focusing exclusively on rational cognition rather than on the role of emotion in psychopathology. The Emotional Schema Therapy (EST) approach advances a model of how people think about and respond to their own emotions and those of others. Drawing on Beck’s schema model, the metacognitive model of Adrian Wells, the Acceptance and Commitment Model (ACT), and social cognitive theory, the EST model suggests that beliefs about the duration, controllability, legitimacy, normalcy, shame and guilt about emotions result in problematic strategies for coping with emotion, such as suppression, avoidance, substance abuse, and rumination. I outline some of the main points of EST and the research supporting the model.